(untitled) (Proceedings of International Conference on Educational Discoveries and Humanities, 2022)
Warehouses of primary and main storage are of great importance in the cultivation of agricultural products, safe and high-quality storage, processing and efficient use of available resources, while ensuring the demand of the population for agricultural products in all seasons of the year. Storage warehouses are artificially created and constantly controlled storage facilities for products, usually creating a low-temperature microclimate. The main task of storage warehouses is to create the regulatory climate necessary to slow down the ripening period of the product, in this process it is necessary to use modern and energy-efficient devices.